Algas fitoplanctónicas de ambientes lénticos y lóticos de la cuenca del Río Salado: tolerancia a factores físicos - Carrillo,U. (2009)
The objective of this paper was to evaluate relationships between phytoplankton algae density and physical factors such as conductivity and temperature in lentic and lotic environments of Salado River basin. The information was obtained from 352 samples taken in San Miguel del Monte shallow lake, in the seepage Lacombe and in the Salado River (main channel and tributaries). Species with density higher than 4.000 individuals ml-1 were selected: eight cyanobacteria, four chlorophytes, three diatoms and one cryptomonadal. Temperature and conductivity optima and tolerance of species temperature were calculated. The chlorophytes showed highest optima temperature average (18,84 ºC) than the cyanobacteria (17,96 ºC) and diatoms (16,31 ºC). Optima temperature of Cryptomonas pusilla was high (19,86ºC). Diatoms and cryptomonadales showed conductivity optima average (5514 and 5599 μS cm-1) higher than chlorophytes and cyanobacteria (4506 and 3508 μS cm-1). Aphanocapsa delicatissima showed markedly low conductivity optima in the lakes (2002 μS cm-1) respect to the obtained in the Salado River (8989 μS cm-1). It must be emphasized that ranges observed in lotic environments were wider than those in lentic environments. The species optima may be useful for future interpretations of the phytoplankton ecology and also as biological indicator for waterquality assessment in the studied environments.